Effects of V2O5 addition on the synthesis of columnar self-reinforced mullite porous ceramics. Issue 8 (15th April 2021) - Li, Kezhuo; Ge, Shengtao; Yuan, Gaoqian; Zhang, Haijun; Zhang, Jun; He, Jiangfeng; Jia, Quanli; Zhang, Shaowei
Abstract: Spearhead columnar mullite was synthesized by in-situ reaction with V2 O5 as additive. When the content of V2 O5 was 7 wt%, the length of the spearhead columnar mullite was the longest with an aspect ratio of about 3.5. Furthermore, columnar self-reinforced mullite porous ceramics were prepared by a foam-gelcasting method, and the effects of V2 O5 content on the rheological and gelling properties of mullite slurries as well as the microstructure, physical property and thermal insulation property of the prepared mullite porous ceramics were studied. The results showed that the flexural strength and compressive strength of the porous ceramics with 63% porosity prepared by using 2 wt% V2 O5 additive were respectively as high as 13.9 and 41.3 MPa, and the thermal conductivity was about 1.04 W m −1  K −1 .